Pharmacodynamic effects of the oral glucokinase activator AZD6370 after single doses in healthy volunteers assessed with euglycaemic clamp. Issue 1 (9th September 2012) - Sjöstrand, M.; Ericsson, H.; Hartford, M.; Norjavaara, E.; Eriksson, J. W.
Abstract Aims This study evaluated the safety, tolerability, pharmacokinetics and pharmacodynamic effects of the glucokinase activator (GKA) AZD6370 in non‐diabetic subjects, using the euglycaemic clamp to avoid the risk of hypoglycaemia. Methods Oral single ascending doses of AZD6370 10–650 mg or subcutaneous short‐acting insulin 4 or 12 U were given to healthy fasting subjects. AZD6370 safety, tolerability and pharmacokinetics were assessed. Pharmacodynamic effects on serum (S)‐insulin and glucose infusion rate (GIR) were investigated with euglycaemic clamp. AZD6370 10–20 mg was also assessed when taken with food without euglycaemic clamp. Results AZD6370 was well tolerated and no safety concerns were raised. AZD6370 was rapidly absorbed and eliminated, and plasma concentration was proportional to dose. Both S‐insulin and GIR increased following AZD6370 administration. The observed increase in GIR correlated with increasing AZD6370 area under the plasma concentration vs. time curve, demonstrating a dose‐concentration‐dependent pharmacodynamic effect. AZD6370 at doses of 50 and 80 mg had similar effects to short‐acting insulin 4 U on peripheral S‐insulin levels but greater effects on GIR, suggesting an effect beyond the increase of peripheral S‐insulin levels at lower doses. In the food interaction part of the study, performed without euglycaemic clamp, dose escalation was stopped at a low dose (20 mg) because of hypoglycaemia. Conclusion The euglycaemic clamp was successfully used to avoid hypoglycaemia and to demonstrate pharmacodynamic effects, that is, markedly increased insulin secretion and glucose utilisation, following administration of AZD6370 in healthy fasting subjects. In addition to the effect on pancreatic insulin secretion, the data support an extra‐pancreatic (hepatic) component of GKA action.